Experimental determination of water droplet "strain cycles" characteristic in the gas area; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 82 : Thermophysical Basis of Energy Technologies - Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Volkov R. S. Roman Sergeevich; Zabelin M. V. Maksim Valerievich (2015, 2015)
Title screen